2007
DOI: 10.2478/v10032-007-0027-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drip Irrigation, N-Fertigation and Cultivation Methods on the Yield and Quality of Carrot

Abstract: Effect of Drip Irrigation, N-Fertigation and Cultivation Methods on the Yield and Quality of Carrot In the years of 2004-2006 research on influence of surface and subsurface drip irrigation on yield and quality of carrot grown on ridges and on the flat ground was investigated. Irrigation was started at soil water potential of 30-40 kPa. Nitrogen fertilizers (100 kg.ha-1) were applied in two rates. The first rate was preplant applied, the second was used by fertigation. In the control treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…The content of minerals (N, P, K, Ca, Mg, Na) in carrot roots found in the present experiment was close to the standard values and similar to the results obtained by other authors (KaacK et al 2001, Dyśko, KaniSzewSKi 2007, majKowSKa-gadomSKa, wierzbicKa 2010, Smoleń et al 2012. The growth stimulators used in the experiment did not have a major effect on the content of total nitrogen, phosphorus and potassium in carrot roots.…”
Section: Resultssupporting
confidence: 92%
“…The content of minerals (N, P, K, Ca, Mg, Na) in carrot roots found in the present experiment was close to the standard values and similar to the results obtained by other authors (KaacK et al 2001, Dyśko, KaniSzewSKi 2007, majKowSKa-gadomSKa, wierzbicKa 2010, Smoleń et al 2012. The growth stimulators used in the experiment did not have a major effect on the content of total nitrogen, phosphorus and potassium in carrot roots.…”
Section: Resultssupporting
confidence: 92%
“…These findings were confirmed by research by Elkner and Kaniszewski (1995) in which drip irrigation decreased the amount of carbohydrates, fibre and nitrates in tomato fruits. Dyśko and Kaniszewski (2007) found that surface and subsurface irrigation decreased dry matter content and total N content in carrot roots.…”
Section: Resultsmentioning
confidence: 97%
“…In the studies by Rolbiecki et al (2003), the yields of carrot were significantly higher, both in dry and wet years. The positive effect of drip irrigation on the yield of carrots grown on flat ground and ridges was also obtained by Dyśko & Kaniszewski (2007), with surface irrigation giving better results than subsurface irrigation in the cultivation on ridges. When growing parsnip, both surface and subsurface irrigation significantly increased the size of the crop and its quality, reducing the number of forked and deformed roots in comparison with the control combination without irrigation (Kaniszewski & Dyśko 2008).…”
Section: Introductionmentioning
confidence: 86%